2016
DOI: 10.3791/54365
|View full text |Cite
|
Sign up to set email alerts
|

Novel Production Protocol for Small-scale Manufacture of Probiotic Fermented Foods

Abstract: A novel dried bacterial consortium of Lactobacillus rhamnosus yoba 2012 and Streptococcus thermophilus C106 is cultured in 1 L of milk. This fresh starter can be used for the production of fermented milk and other fermented foods either at home or at small-scale in rural settings. For the fresh starter, 1 L of milk is pasteurized in a pan that fits into a larger pan containing water, placed on a source of heat. In this water bath, the milk is heated and incubated at 85 °C for 30 min. Thereafter, the milk is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The increasing popularity and attention for probiotics in the western world by both consumers and the scientific world, and the associated growth in probiotic products, cannot be replicated directly in Africa. Hence, the intervention that enables local communities to produce and sell their own probiotic yoghurts was tailored to the local circumstances in a continuous process of searching for appropriate solutions [16,[71][72][73][74][75]. The production of locally produced probiotic yoghurt by means of an affordable shelf stable bacterial starter culture can be seen as a bottom-up innovation that complies with local needs and capabilities, facilitates employment, increases purchasing power and improves access for many people to an affordable, tasty and healthy product that can be part of the daily diet.…”
Section: Evaluation Of Economic and Political Related Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The increasing popularity and attention for probiotics in the western world by both consumers and the scientific world, and the associated growth in probiotic products, cannot be replicated directly in Africa. Hence, the intervention that enables local communities to produce and sell their own probiotic yoghurts was tailored to the local circumstances in a continuous process of searching for appropriate solutions [16,[71][72][73][74][75]. The production of locally produced probiotic yoghurt by means of an affordable shelf stable bacterial starter culture can be seen as a bottom-up innovation that complies with local needs and capabilities, facilitates employment, increases purchasing power and improves access for many people to an affordable, tasty and healthy product that can be part of the daily diet.…”
Section: Evaluation Of Economic and Political Related Factorsmentioning
confidence: 99%
“…The characteristics of the probiotic starter culture and its specific use have recently been described [73,74]. In short, the dried starter culture consists of L. rhamnosus yoba 2012 and an adjuvant strain Streptococcus thermophilus C106.…”
Section: Production Of Probiotic Yoghurtmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequence comparison could confirm that all technical and functional properties attributed to the original strain exist with the same level of certainty in the Yoba 2012 strain as in actual commercial clones of L. rhamnosus GG, branded as LGG® (Kort and Sybesma, 2012). They then created a two-strain sachet containing Yoba 2012 plus a Streptococcus thermophilus C106 strain that was highly efficient at fermenting milk Westerik et al, 2016). They showed that a 1 gram sachet could produce 100 litres of probiotic fermented milk, including the propagated L. rhamnosus Yoba strain.…”
Section: East Africamentioning
confidence: 92%